Reliability and validity of the Four Square Step Test in patients with hip osteoarthritis before and after total hip replacement - Batting, M; Barker, K (Elsevier, 2018)
Objective To determine the validity and inter- and intra-rater reliability of the Four Square Step Test (FSST) in assessing gait performance, balance and physical function for patients with hip osteoarthritis before and after total hip replacement (THR). Design Observational, repeated measures. Setting A specialist orthopaedic hospital. Participants Fifty-eight participants with moderate to severe hip osteoarthritis scheduled to receive primary hip replacement within 4 months from recruitment. Main outcome measure Time to complete the FSST, time and steps to complete the Figure of 8 Walk Test (F8W) and Berg Balance Scale score (BBS). Results The Bland and Altman limits of agreement for intra-rater measurements of the FSST were −3.2 s to 3.5 seconds before THR and −1.5 to 2.0 seconds after THR. Limits of agreement for two different raters were −2.2 to 3.4 seconds, all with small mean differences indicating little bias between raters or replications. Concurrent validity was assessed, and the FSST correlated highly with the F8W (r = 0.7, P < 0.001) and moderately with the BBS (r = 0.6, P < 0.001). Only one participant was rated as being at moderate risk of falls on the BBS, with the other participants scoring low; only one participant failed to complete the F8W. This is in contrast to the FSST, which 21 people failed to complete pre-operatively. Conclusions The FSST is a valid and reliable measure of multi-directional stepping speed and balance, giving a more informative measure of gait performance than the F8W and BBS, and is feasible for use in a clinical population of patients both before and after THR.